2019
DOI: 10.1097/hjh.0000000000001844
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of proximal ascending aorta and target organ damage in hypertensive patients

Abstract: Prevalence of ascending aorta dilatation in hypertensive patients reaches 13%. Hypertensive individuals with enlarged ascending aorta showed significantly increased left ventricular mass, a well known sign of hypertension related cardiac damage and could thus represent a subset of hypertensive patients at an increased cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Patients with AADa showed a higher rate of established cardiovascular risk factors, such as LVH, LAe and PWV more than 10 m/s, supporting previous evidences of a role of AAD in cardiovascular risk stratification [1,8]. In particular LVMi, arterial stiffness (in terms of PWV) and ASC dimension could be considered as three different anatomical expression of the same adaptive phenomenon.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Patients with AADa showed a higher rate of established cardiovascular risk factors, such as LVH, LAe and PWV more than 10 m/s, supporting previous evidences of a role of AAD in cardiovascular risk stratification [1,8]. In particular LVMi, arterial stiffness (in terms of PWV) and ASC dimension could be considered as three different anatomical expression of the same adaptive phenomenon.…”
Section: Discussionsupporting
confidence: 77%
“…Hypertension, such as ageing, are associated with an increase in arterial stiffness (in form of PWV) [17], affecting the summation between incident and reflexed pulse pressure waves at aortic root level [18,19]. This complex interplay leads to a mismatch between cardiac output and vascular impedance with consequent LVH and AAD, as recently suggested [8,20].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The prevalence of proximal aortic dilatation in hypertensive population varies from study to study owing to the differences in enrolled subjects (especially age), definition of aortic dilatation, and imaging methods. The prevalence ranged from 6.1 to 19% [3,8,32,33]. A meta-analysis including 10 791 hypertensive patients showed that the overall prevalence of echocardiographic aortic root dilation (ARD) was 9.1%, with a marked difference between men and women (12.7 versus 4.5%, P < 0.001) [3].…”
Section: Prevalence Of Proximal Aorta Dilatation In Hypertensionmentioning
confidence: 99%
“…[3] Central blood pressure (cBP) is superior to bBP. [4] Central hemodynamics like cardiac output (CO) adds significantly to the details about the ultimate heart pumping. Arterial stiffness, similarly, is a gold standard in hypertension and measured in forms of pulse-wave velocity and augmentation index.…”
Section: Introductionmentioning
confidence: 99%